Sampling and collecting foliage elements for the determination of the foliar nutrients in ICOS ecosystem stations - Loustau, Denis; Altimir, Nuria; Barbaste, Mireille; Gielen, Bert; Jiménez, Sara Marańón; Klumpp, Katja; Linder, Sune; Matteucci, Giorgio; Merbold, Lutz; Beek, Marteen Op de; Soulé, Patrice; Thimonier, Anne; et al. (Walter de Gruyter GmbH, 2018)
The nutritional status of plant canopies in terms of nutrients (C, N, P, K, Ca, Mg, Mn, Fe, Cu, Zn) exerts a strong influence on the carbon cycle and energy balance of terrestrial ecosystems. Therefore, in order to account for the spatial and temporal variations in nutritional status of the plant species composing the canopy, we detail the methodology applied to achieve consistent time-series of leaf mass to area ratio and nutrient content of the foliage within the footprint of the Integrated Carbon Observation System Ecosystem stations. The guidelines and defi-nitions apply to most terrestrial ecosystems.